Interpreting pathways to discover cancer driver genes with Moonlight - Antonio Colaprico (Nature Portfolio, 2020)
Identification of cancer driver genes, especially those that can act as tumour suppressors or oncogenes depending on context, remains a challenge. Here, the authors introduce Moonlight, a tool that integrates multi-omic data to address this challenge and identify numerous dual-role cancer genes.